Keefektifan Kalimat Dalam Teks Berita Siswa Kelas VIII SMP Negeri 2 Bayang - Yola Gustifa; Dewi Anggraini (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to describe the effectiveness of ``sentences in news texts for Grade VIII students of SMP Negeri 2 Bayang. This type of research is a qualitative research with descriptive method. The background of this research was conducted at SMP Negeri 2 Bayang, in class VIII to be precise. The entries in this study were in the form of news texts for class VIII students which were viewed from two indicators, namely the accuracy of reasoning and the accuracy of language. Presence in this study as a data collection instrument (human instrument). The data collection technique used is the fishing technique.The results of the study proved that from the sentences analyzed, some sentences were found to be effective and most sentences were not. Sentences are classified as effective because they fulfill two conditions, namely the accuracy of reasoning and the accuracy of language. Most sentences are ineffective because they do not meet the requirements for the accuracy of reasoning and linguistic accuracy due to spelling inaccuracies.